Laboratory and Field Evaluation of some Bio and Chemical Insecticides Against Nymphs and Adults of Ceroplasts Rusci L. (Coccidae: Hemiptera) - Sh. Mansor, M.; Mohamed Hashem, Nayef (International Journal of Engineering and Technology, 2018)
The present work including laboratory and field experimental test to evaluate the efficiency of different insecticides (systemic and biocides). Laboratory works including different concentrations for Mitrixin, Levo, Evisect, Polo and Actara for Ceroplasts rusci L. insect in leaf. Mortality percentage reading after two days. Field works were including the best concentration of insecticides achieved the highest mortality percentage for nymphs and adults of Ceroplasts rusci in the tree. The Mortality percentage reading after one, two, seven, fourteen days.Laboratory results showed that the efficiency of insecticides significantly variant is depending to concentration and type of insecticides. The corrected Mortality percentage was increased by increasing the concentration and type of insecticides. The Mortality percentage (59.23, 53.94, 52.25) insect/leaf increase for insecticides (Mitrixin, Levo, Evisect) respectively. In a field study, the effect of insecticide toxicity for nymphs and adults ofÂ  C. rusci L. (Coccidae: Hemiptera) was tested. The Results showed that the insecticides Mitrixin distinction in the after two weeks treatment and levo insecticide in after a day treatment and after two weeks treatment while the lethal rate is (64.32, 63.49, 58.73) insect/leaf inÂ  (Matrixin, Levo, Evisect), respectively.Â